Design and implementation of OSPF vulnerability analysis and detection system - Zun-ying QIN; Guo-dong LI; Wei LI; Xu-chang HUANG (Tongxin xuebao)
A universal and multi-mode OSPF vulnerability detection system was designed based on analysis and research of OSPF vulnerability.The system implements denial of service attack model with the method of forging entity router and man-in-middle attack model with zero-copy technology.The method combining SNMP and bypass monitoring was adopted to achieve real-time monitoring of test results.Finally,the system proves the vulnerability of different types of routing equipments in the test environment and the vulnerability hazards were analyzed quantitatively.